2008
DOI: 10.1080/00365540802308431
|View full text |Cite
|
Sign up to set email alerts
|

Congenital CMV infection: Prevalence in newborns and the impact on hearing deficit

Abstract: Congenital cytomegalovirus (CMV) infection is asymptomatic in 90% of infected newborns but approximately 10-20% of these infants are at risk of developing sequelae later, mostly hearing deficit. The aims of the study were to investigate the prevalence of congenital CMV infection in a Swedish population of newborns and investigate the relative risk of hearing deficit in newborns with congenital CMV infection. The dried blood spot (DBS) samples of 6060 newborns in southern Stockholm during 12 months (October 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 24 publications
3
37
0
1
Order By: Relevance
“…This result is comparable with the prevalence established in similar prospective studies in the neighboring countries of Italy (0.18%; 95% CI, 0.09-0.26%) [Barbi et al, 2006] and Austria (0.21%) [Halwaschs-Baumann et al, 2000], and some other industrialized countries such as Sweden (0.20%; 95% CI, 0.1-0.3%) [Engman et al, 2008], Japan (0.17-0.19%) [Yamagashi et al, 2006;Endo et al, 2009] and the Netherlands (0.09%; 95% CI, 0.04-0.19%) [Gaytant et al, 2005]. Some other studies from the above mentioned countries showed higher prevalence of congenital CMV infection (Italy 0.47%; 95% CI, 0.22-1.00% [Barbi et al, 1998], Sweden 0.46%; 95% CI, 0.37-0.58% [Ahlfors et al, 1999], Japan 0.66%; 95% CI, 0.27-1.70% [Kamada et al, 1983] and 0.31%; 95% CI, 0.22-0.43% [Numazaki and Fujikawa, 2004]), however, due to their design they may suffer from selection bias.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This result is comparable with the prevalence established in similar prospective studies in the neighboring countries of Italy (0.18%; 95% CI, 0.09-0.26%) [Barbi et al, 2006] and Austria (0.21%) [Halwaschs-Baumann et al, 2000], and some other industrialized countries such as Sweden (0.20%; 95% CI, 0.1-0.3%) [Engman et al, 2008], Japan (0.17-0.19%) [Yamagashi et al, 2006;Endo et al, 2009] and the Netherlands (0.09%; 95% CI, 0.04-0.19%) [Gaytant et al, 2005]. Some other studies from the above mentioned countries showed higher prevalence of congenital CMV infection (Italy 0.47%; 95% CI, 0.22-1.00% [Barbi et al, 1998], Sweden 0.46%; 95% CI, 0.37-0.58% [Ahlfors et al, 1999], Japan 0.66%; 95% CI, 0.27-1.70% [Kamada et al, 1983] and 0.31%; 95% CI, 0.22-0.43% [Numazaki and Fujikawa, 2004]), however, due to their design they may suffer from selection bias.…”
Section: Discussionsupporting
confidence: 93%
“…In similar previous studies, the prevalence at birth in Israel and Brasil were 0.7% and 1.1% (95% CI, 0.86-1.33%), respectively [Schlesinger et al, 2003;Mussi-Pinhata et al, 2009]. In the great majority of prevalence studies published to date, DBS have been used for PCR screening, prospectively or retrospectively [Barbi et al, 2006;Yamagashi et al, 2006;Engman et al, 2008;Boppana et al, 2010;Kharrazi et al, 2010]. PCR protocols for the detection of CMV DNA in DBS were first developed for retrospective diagnosis of congenital CMV infection in infants and children with hearing loss or other congenital CMV-related symptoms, which had not been diagnosed at birth [Johansson et al, 1997;Barbi et al, 2000Barbi et al, , 2006Yamamoto et al, 2001].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Studies employing a range of methods for CMV DBS testing have reported widely varying sensitivities of 50-100%. (Barbi et al 2008;Engman et al 2008;Soetens et al 2008;Choi et al 2009a, b) Some studies showing 100% sensitivity used DBS samples from infants already diagnosed with congenital CMV, either on clinical grounds or by culture techniques, which would overrepresent infants with higher CMV viral loads and thus produce artificially high estimates of sensitivity. Two DBS studies tested unselected samples of infants and also collected either urine or saliva for comparative testing and reported DBS testing sensitivities of 70-80% and specificities of 99-100%.…”
Section: Infrastructure and Laboratory Methods For CMV Newborn Screeningmentioning
confidence: 97%